Antimicrobial potential and in vitro cytotoxicity study of polyvinyl pyrollidone‐stabilised silver nanoparticles synthesised from Lysinibacillus boronitolerans. Issue 4 (4th June 2021) - Bhatia, Divya; Mittal, Ashwani; Malik, Deepak Kumar
Abstract: The main emphasis herein is on the eco‐friendly synthesis and assessment of the antimicrobial potential of silver nanoparticles (AgNPs) and a cytotoxicity study. Silver nanoparticles were synthesised by an extracellular method using bacterial supernatant. Biosynthesised silver nanoparticles were characterised by UV‐vis spectroscopy, transmission electron microscopy (TEM), Fourier transform infrared spectroscopy, dynamic light scattering, and zeta potential analysis. The synthesised silver nanoparticles exhibited a characteristic peak at 420 nm. TEM analysis depicted the spherical shape and approximately 20 nm size of nanoparticles. Silver nanoparticles carry a charge of −33.75 mV, which confirms their stability. Biogenic polyvinyl pyrrolidone‐coated AgNPs exhibited significant antimicrobial effects against all opportunistic pathogens (Gram‐positive and Gram‐negative bacteria, and fungi). Silver nanoparticles equally affect the growth of both Gram‐positive and Gram‐negative bacteria, with a maximum inhibition zone observed at 22 mm and a minimum at 13 mm against Pseudomonas aeruginosa and Fusarium graminearum, respectively. The minimum inhibitory concentration (MIC) of AgNPs against P. aeruginosa and Staphylococcus aureus was recorded at between 15 and 20 μg/ml. Synthesised nanoparticles exhibited a significant synergistic effect in combination with conventional antibiotics. Cytotoxicity estimates using C2C12 skeletal muscle cell line via 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) test and lactate dehydrogenase assay were directly related to the concentration of AgNPs and length of exposure. On the basis of the MTT test, the IC50 of AgNPs for the C2C12 cell line was approximately 5.45 μg/ml concentration after 4 h exposure.